2021
DOI: 10.1124/molpharm.121.000415
|View full text |Cite
|
Sign up to set email alerts
|

New Synthetic Caffeine Analogs as Modulators of the Cholinergic System

Abstract: Alzheimer's disease (AD) is a multifactorial neurodegenerative disorder. Since cholinergic deficit is a major factor in this disease, two molecular targets for its treatment are the acetylcholinesterase (AChE) and the nicotinic acetylcholine receptors (nAChRs). Given that caffeine is a natural compound that behaves as an AChE inhibitor and as a partial agonist of nAChRs, the aim of this work was to synthetize more potent bifunctional caffeine analogs that modulate these two molecular targets. To this end, a th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 66 publications
2
23
0
Order By: Relevance
“…Differences in K D values from samples before and after incubation with carb indicate different conformational states of the receptor and, indirectly, functional response of the nAChR to carb. 30,31 We observed that, when caffeine analogues were incubated with carb, the K D values were similar in all cases, indicating that receptor desensitization occurred (Figure 6). However, in the absence of carb, we observed that only compound 12 at 1 μM (n = 4) and 100 μM (n = 4) caused conformational changes of the nAChR, stabilizing it in a desensitized state (Figure 6).…”
Section: ■ Results and Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Differences in K D values from samples before and after incubation with carb indicate different conformational states of the receptor and, indirectly, functional response of the nAChR to carb. 30,31 We observed that, when caffeine analogues were incubated with carb, the K D values were similar in all cases, indicating that receptor desensitization occurred (Figure 6). However, in the absence of carb, we observed that only compound 12 at 1 μM (n = 4) and 100 μM (n = 4) caused conformational changes of the nAChR, stabilizing it in a desensitized state (Figure 6).…”
Section: ■ Results and Discussionmentioning
confidence: 77%
“…The reduction of the mean open time by the increase of the compound concentration could be due to an open channel block as described for caffeine and compound 9. 30,31 In contrast to the low activity of the former analogues, high channel activity was detected with compounds 12 and 15. Although the frequency of openings was high in the presence of both compounds, clusters could not be distinguished.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
See 3 more Smart Citations